Contribution to gender and social inclusion strategy for the cashew value chain in Golfo de Fonseca, Honduras - CGIAR Research Program on Policies, Institutions, and Markets (2021)
This strategy was developed by Swisscontact with support from the Alliance of Bioversity International and CIAT to improve women's empowerment in the production and processing nodes of the cashew chain.